Metode Penafsiran Ibn Kathîr dalam Tafsîr al-QurâÃ¢n al-Azim - Aruf, Thohir (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
When the Koran was revealed, the Prophet Muhammad serves as mubayyin, explained to his companions about the meaning and content of the verses of the Koran, particularly concerning the verses that are not understood or vague meaning. After the Prophetâs death, the friends do ijtihâd in understanding the verses of the Koran to address new issues that arise, especially those who have the ability like âAlÃ® b. Abî Tâlib, Ibn âAbbÃ¢s, Ubay b. Kaâb and Ibn MasâÃ»d. it is understood that the Tafsîr Ibn Kathîr is one interpretation, which, when viewed in terms of its interpretation is the interpretation of analytical methods decompose (tahlîlî). Meanwhile, when the terms of the sources of interpretation, it is a bi al-maâthÃ»r interpretation. But unlike other interpretations, in this interpretation the author has made criticism of the assessment of transmitters of hadith or athar friends, and have downloaded the Legal Affairs Committee (reinforce) opinion one of several different opinions, so this interpretation when viewed from a history that is mentioned more accounted